Preventing Ischial Pressure Ulcers: III. Clinical Pilot Study of Chronic Neuromuscular Electrical Stimulation - Hilton M. Kaplan; Lucinda L. Baker; Salah Rubayi; Gerald E. Loeb (Applied Bionics and Biomechanics)
Objective: BIONs™ (BIOnic Neurons) are injectable, wireless microstimulators that make chronic BION Active Seating (BAS) possible for pressure ulcer prevention (PUP). Neuromuscular electrical stimulation (NMES) produces skeletal motion and activates trophic factors, counteracting three major etiological mechanisms leading to pressure ulcers (PUs): immobility, soft-tissue atrophy, and ischemia. Companion papers I and II reviewed prior experience with NMES for PUP, and analyzed the biomechanical considerations, respectively. This paper presents a treatment strategy derived from this analysis, and the clinical results of the first three cases.